PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IV SD NEGERI 18 SUNGAI PAKNING - Yunidar, Selfi; Noviana, Eddy; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of this research is the weakness of student’s learning result of social subject. It show from 30 student’s, 20 students (66,67%) have lower score, and it is only 10 student’s (33,33%) have average score 59,5. The KKM of this school is 73. According to that problem, the research by implementing sooperative learning model Take and Give. In cycle 1, the percentage of teachers activity in first meeting is adequate 75% with good category. In second meeting, teachers activity significantly increased to 79,16% with good category. In cycle 2, first meeting was in very good category 83,33% and second meeting indicated a very good category 91,66%. Meanwhile, the activity of student’s also improved. In cycle 1 indicated 58,33% in adequate category and in cycle 2 has increased up to 75% with good category. In cycle 2, first meeting, the activity of student’s has been increasing to 87,5% with very good category and second meeting indicated very good category 95,83%. An average score of student’s learning sesult before implementation is 59,5. It increased to 68,83 in cycle 1, and 69,83 incycle 2. In classical completensess, cycle 1 and cycle 2 were achieved. In conclusion, implementation cooperative learning model Take and Give can improve student’s learning result of fourth grade student of SD Negeri 18 Sungai Pakning in PKn subject.Key words :Cooperative model Take and Give, learning result of PKn subject.